2005
DOI: 10.1177/0193841x05279180
|View full text |Cite
|
Sign up to set email alerts
|

Redistributing Wealth to Families

Abstract: This study aims to shed light on the main characteristics of the French system for redistributing wealth to families through tax revenues and social transfers. For the purposes of this exercise, the authors used the MYRIADE microsimulation model, which covers most of the redistribution system, though it is limited to monetary flows such as family benefits, housing allowances, minimum social welfare payments, income tax, and tax on furnished accommodation. The authors used a particular methodology to highlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 5 publications
1
6
1
Order By: Relevance
“…29. Which is consistent with previous studies conducted in this period: Laroque and Salanié (1999and Legendre et al (2003 for 2000 find a U-shaped EMTR distribution, whereas Bourguignon (1998) ➔ with the positive marginal rates of the PPE in its degressive phase (see Online complement C4, Figure C4-II). 30 For the EPTR, the findings are different.…”
Section: Changes In Emtr and Eptr Between 1998 2008 And 2014supporting
confidence: 92%
See 4 more Smart Citations
“…29. Which is consistent with previous studies conducted in this period: Laroque and Salanié (1999and Legendre et al (2003 for 2000 find a U-shaped EMTR distribution, whereas Bourguignon (1998) ➔ with the positive marginal rates of the PPE in its degressive phase (see Online complement C4, Figure C4-II). 30 For the EPTR, the findings are different.…”
Section: Changes In Emtr and Eptr Between 1998 2008 And 2014supporting
confidence: 92%
“…He found that the EMTR curve had a flattened U shape, but with peaks at certain deciles. Laroque and Salanié (1999), and Legendre et al (2003) calculated EMTR at the end of the 1990s and obtained similar findings to Bourguignon (a more-or-less U-shaped curve), but they also calculated return-to-work incentive indicators. 8 Chanchole and Lalanne (2012) gave an overview of EMTR in 2009, calculated on the basis of net earned income and replacement and capital income, but not taking into account social contributions.…”
Section: See the Literature Review Bymentioning
confidence: 54%
See 3 more Smart Citations